2013
DOI: 10.1007/s10554-013-0254-2
|View full text |Cite
|
Sign up to set email alerts
|

The amount of dysfunctional but viable myocardium predicts long-term survival in patients with ischemic cardiomyopathy and left ventricular dysfunction

Abstract: To evaluate the prognostic significance of combined myocardial perfusion SPECT and [18F]FDG PET viability scanning for the prediction of survival in patients with ischemic cardiomyopathy (iCMP) and left ventricular dysfunction. 244 patients (64.0 ± 10.6 years, 86 % men) with iCMP and LVEF ≤ 45 % underwent SPECT/PET. Percent scar tissue and SPECT/PET-mismatch (%-mismatch) were calculated and correlated with event-free survival according to the type of therapy (medical therapy with/out revascularization) provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…Pixels of perfusion defect with counts [ 2 standard deviations below gender matched normal limits database are considered nonviable. 145 Notably, the extent of viability (greater than 10% hibernating myocardium) 146 is an important determinant of recovery of LV function Optional Semiquantitative (small, 1-2 segments; medium 3-4 segments; large C 5 segments) Required Quantitative (small \10%; medium 10-20%; large C20%) Required Severity Qualitative (mild, moderate, severe, absent tracer uptake) Optional Semiquantitative (score 0 = normal; mild or score 1 = 10% to \25% count reduction; moderate or score 2 = 25% to \50% count reduction; severe or score 3 = C50% reduction in counts; severe or score 4 (background counts) Required Quantitative (computer generated scores) Recommended Reversibility (fixed = no reversibility; mildly reversible; moderately reversible; predominantly reversible; predominantly fixed) Table 9 lists the threshold values and the physiological basis for determination of myocardial viability using clinically used radionuclides.…”
Section: Myocardial Viabilitymentioning
confidence: 99%
“…Pixels of perfusion defect with counts [ 2 standard deviations below gender matched normal limits database are considered nonviable. 145 Notably, the extent of viability (greater than 10% hibernating myocardium) 146 is an important determinant of recovery of LV function Optional Semiquantitative (small, 1-2 segments; medium 3-4 segments; large C 5 segments) Required Quantitative (small \10%; medium 10-20%; large C20%) Required Severity Qualitative (mild, moderate, severe, absent tracer uptake) Optional Semiquantitative (score 0 = normal; mild or score 1 = 10% to \25% count reduction; moderate or score 2 = 25% to \50% count reduction; severe or score 3 = C50% reduction in counts; severe or score 4 (background counts) Required Quantitative (computer generated scores) Recommended Reversibility (fixed = no reversibility; mildly reversible; moderately reversible; predominantly reversible; predominantly fixed) Table 9 lists the threshold values and the physiological basis for determination of myocardial viability using clinically used radionuclides.…”
Section: Myocardial Viabilitymentioning
confidence: 99%
“…The presence of viability by any imaging modality (although mainly DSE and nuclear techniques) appeared to confer a significantly improved outcome in those undergoing revascularisation. These values were considerably higher than the mismatch threshold of 7% for PET identified in the substudy of PET and Recovery following Revascularisation (PARR-2) study [81] (discussed below) and of >5% in another retrospective analysis [82], highlighting the uncertainty in this area and the limitations of retrospective data. The beneficial effect of revascularisation on survival in patients with viability appeared to correlate to the severity of LV dysfunction.…”
Section: Heart Failure and Ischaemic Heart Disease -To Revascularise mentioning
confidence: 76%
“…In a subsequent substudy of PARR-2 trial, the investigators found that in 182 patients with ischemic LV dysfunction, the risk for cardiac death, myocardial infarction or cardiac-related re-hospitalization is reduced when a quantitative mismatch variable is above 7% (28). Quantitative analysis of mismatch and scar was also recently applied by Ubleis et al (29) in 244 patients to evaluate the prognostic significance of 18 FDG PET viability scanning for the prediction of patients with ischemic cardiomyopathy and left ventricular dysfunction. Their analysis has shown that the patients with mismatch greater than 5% (as established by the quantitative software) who did not undergo early revascularization had significantly higher mortality than the group who had similar mismatch (≥ 5%) and did undergo the intervention.…”
Section: Viability Quantificationmentioning
confidence: 99%